2018
DOI: 10.1007/s00540-018-2451-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and functional analysis of the RYR1 mutation p.Thr84Met revealed a susceptibility to malignant hyperthermia

Abstract: Our results of functional testing indicated RYR1 hypersensitivity to caffeine and 4CmC. We conclude that the genetic variant was associated with MH susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In this study, G1530T in CACNA1S was suggested to be pathogenic by 6 prediction software, and C4615T was suggested to be pathogenic by 5 prediction software. (Table 3) (3,14,15). Recent evidence has also con rmed the foresight of requiring functional analysis of missense variants before their adoption for diagnostic use (14).…”
Section: Resultsmentioning
confidence: 97%
“…In this study, G1530T in CACNA1S was suggested to be pathogenic by 6 prediction software, and C4615T was suggested to be pathogenic by 5 prediction software. (Table 3) (3,14,15). Recent evidence has also con rmed the foresight of requiring functional analysis of missense variants before their adoption for diagnostic use (14).…”
Section: Resultsmentioning
confidence: 97%
“…1 T84M and Q155K were functionally analysed in a previous study and have been suggested to contribute to MH crisis. 16,17 Using a modified version of the American College of Medical Genetics and Genomics guidelines, 18 the T84M and Q155K variants can be classified as uncertain significance and likely pathogenic, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…MH can be diagnosed clinically, which evaluates clinical presentation and laboratory findings, or MH can be diagnosed by in vitro testing, which examines the presence or absence of MH susceptibility, including a muscle biopsy and genetic analysis [6][7][8].…”
Section: Introductionmentioning
confidence: 99%